Antiepileptic drug prescribing before, during and after pregnancy: a study in seven European regions†. (13th August 2015) - Charlton, Rachel; Garne, Ester; Wang, Hao; Klungsøyr, Kari; Jordan, Sue; Neville, Amanda; Pierini, Anna; Hansen, Anne; Engeland, Anders; Gini, Rosa; Thayer, Daniel; Bos, Jens; et al.
Abstract: Purpose: The aim of this study was to explore antiepileptic drug (AED) prescribing before, during and after pregnancy as recorded in seven population‐based electronic healthcare databases. Methods: Databases in Denmark, Norway, the Netherlands, Italy (Emilia Romagna/Tuscany), Wales and the Clinical Practice Research Datalink, representing the rest of the UK, were accessed for the study. Women with a pregnancy starting and ending between 2004 and 2010, which ended in a delivery, were identified. AED prescriptions issued (UK) or dispensed (non‐UK) at any time during pregnancy and the 6 months before and after pregnancy were identified in each of the databases. AED prescribing patterns were analysed, and the choice of AEDs and co‐prescribing of folic acid were evaluated. Results: In total, 978 957 women with 1 248 713 deliveries were identified. In all regions, AED prescribing declined during pregnancy and was lowest during the third trimester, before returning to pre‐pregnancy levels by 6 months following delivery. For all deliveries, the prevalence of AED prescribing during pregnancy was 51 per 10 000 pregnancies (CI95 49–52%) and was lowest in the Netherlands (43/10 000; CI95 33–54%) and highest in Wales (60/10 000; CI95 54–66%). In Denmark, Norway and the two UK databases lamotrigine was the most commonly prescribed AED; whereas in the Italian and Dutch databases, carbamazepine, valproate and phenobarbital were most frequently prescribed. Few women prescribed with AEDs in the 3 months before pregnancy were co‐prescribed with high‐dose folic acid: ranging from 1.0% (CI95 0.3–1.8%) in Emilia Romagna to 33.5% (CI95 28.7–38.4%) in Wales. Conclusion: The country's differences in prescribing patterns may suggest different use, knowledge or interpretation of the scientific evidence base. The low co‐prescribing of folic acid indicates that more needs to be done to better inform clinicians and women of childbearing age taking AEDs about the need to offer and receive complete preconception care. © 2015 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons Ltd.